Health, well-being and sustainable housing - Prochorskaitė, Agnė; Malienė, Vida (International Journal of Strategic Property Management, 2013)
Sustainability of the built environment is an increasingly prominent concern in academic and policy discussions in the UK and EU. Initiatives such as the Code for Sustainable Homes in the UK have been developed to aid integration of sustainability principles into housing developments. Primary focus in this field has been largely on environmental sustainability (particularly energy efficiency) with less attention paid to social and economic factors. This article argues that health and well-being issues need greater consideration within current sustainable housing policy and developments. Three key reasons are presented in support of this argument: (i) Creation of greater market demand; public demand for sustainable buildings could be enhanced through greater promotion of the health and well-being benefits of sustainable housing: (ii) Time-scales; given the longevity of buildings, health considerations should be of paramount importance to avoid any possible future adverse effects: (iii) Indirect societal benefits; enhanced health and well-being can lead to wider societal and economic benefits such as lower healthcare costs. The paper then presents some of the seminal findings from health and housing literature review, outlining how these can be used to enhance sustainable housing policy and developments. The paper concludes by presenting the next stages of research.First Publish Online: 3 Apr 2013